Where courage is like a wild horse : the world of an Indian orphanage - Skolnick, Sharon, 1944 October 3- (University of Nebraska Press, 1997)
The dreams of a courageous Apache girl illuminate the hidden world of an Indian orphanage in this unforgettable story. Over forty years ago, Sharon Skolnick (Okee-Chee) and her sisters were removed from their Apache parents and became wards of the state of Oklahoma. She and her nearest sister made their way together through the Oklahoma Indian child welfare system. Shuttled back and forth between foster homes and orphanages, they finally ended up at the Murrow Indian Orphanage in Muskogee, Oklahoma. Here, Skolnick tells the gripping and ultimately triumphal account of the year the sisters spent there. Murrow was a place of wonder and terror, friendship and loneliness, where resilient children forged shifting alliances and conspired together yet yearned in solitude for a home and family to call their own. Skolnick paints an absorbing portrait of the world of an Indian orphanage, a world both bright and dark, vividly rendered through a child's eyes but tempered by the perspective of the woman who survived the Indian child welfare system and became an Apache artist.